2020
DOI: 10.1186/s43042-020-00057-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (VDR) gene FokI, BsmI, ApaI, and TaqI polymorphisms and osteoporosis risk: a meta-analysis

Abstract: Background: Osteoporosis is a disease of the bones in which the density of the bones decreases. The prevalence of this disease greatly varies in different populations of the world. Numerous studies have been investigated VDR gene polymorphisms as osteoporosis risk in different ethnic groups. In present meta-analysis, the aim is to find out the role of VDR gene polymorphisms (FokI, BsmI, ApaI, and TaqI) in osteoporosis risk. Methods: Suitable case-control studies for present meta-analysis were retrieved from fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 93 publications
1
14
0
Order By: Relevance
“…ApaI polymorphism was associated with protection against osteoporosis; 23,25 however, there are other studies that find some detrimental effects or no effect at all on osteoporosis. [26][27][28] BsmI polymorphism was associated with an increased risk of osteoporosis, 23 but other authors have not found any association. 28,29 FokI and TaqI were significantly associated with the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ApaI polymorphism was associated with protection against osteoporosis; 23,25 however, there are other studies that find some detrimental effects or no effect at all on osteoporosis. [26][27][28] BsmI polymorphism was associated with an increased risk of osteoporosis, 23 but other authors have not found any association. 28,29 FokI and TaqI were significantly associated with the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 92%
“…[26][27][28] BsmI polymorphism was associated with an increased risk of osteoporosis, 23 but other authors have not found any association. 28,29 FokI and TaqI were significantly associated with the development of osteoporosis. 23,25,28 Fok1 is located in exon 2 of the gene and leads to the formation of a new start codon, resulting in a shorter VDR product that interacts more efficiently with the transcription factor TFIIB.…”
Section: Discussionmentioning
confidence: 92%
“…The original data of all published eligible studies were almost covered by this meta-analysis. However, according to a recently published meta-analysis of Yadav et al [61], in the absence of a subgroup analysis based on the sex and age of patients or the type of osteoporosis, BsmI polymorphism seemed not to be associated with the pathogenesis of osteoporosis. It indicated that possible relationship between VDR gene polymorphisms and osteoporosis may be related to gender, race, and age difference of subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Through sensitivity analysis and publication bias detection, the results of this meta-analysis were true and credible.The original data of all published eligible studies were almost covered by this meta-analysis. However, according to a recently published meta-analysis of Yadav(2020) 59 , in the absence of a subgroup analysis based on the sex and age of patients or the type of osteoporosis, BsmI polymorphism seemed not be associated with the pathogenesis of osteoporosis. It indicated possible the relationship between VDR gene polymorphisms and osteoporosis may be related to gender, race and age difference of subjects.…”
Section: Discussionmentioning
confidence: 97%